Multi-Year Program under Budget Constraints Using Multi-Criteria Analysis - Surya Adiguna; Dewanti Dewanti Dewanti; JB Odoki (Journal of the Civil Engineering Forum, 2017)
Road investment appraisal requires joint consideration of multiple criteria which are related to engineering, economic, social and environmental impacts. The investment consideration could be based on the economic analysis but however for some factors, such as environmental, social, and political, are difficult to quantify in monetary term. The multi-criteria analysis is the alternative tool which caters the requirements of the issues above. The research, which is based on 102 class D and class E paved road sections in Kenya, is about to optimize road network investment under budget constraints by applying a multi-criteria analysis (MCA) method and compare it with the conventional economic analysis. The MCA is developed from hierarchy structure which is considered as the analytical framework. The framework is based on selected criteria and weights which are assigned from Kenya road policy. The HDM-4 software is applied as decision-making tool to obtain the best investment alternatives and road work programs from both MCA and economic analysis. The road work programs will be the results from the analysis using both MCA and economic analysis within HDM-4 software to see the difference and compare the results between both programs. The results from MCA show 51 road sections need periodic work, which is overlay or resealing. Meanwhile, 51 others need rehabilitation or reconstruction. The five years road work program which based on economic analysis result shows that it costs almost Kenyan Shilling (KES) 130 billion to maintain the class D and E paved road in Kenya. Meanwhile, the MCA only requires KES 59.5 billion for 5 years program. These results show huge margin between two analyses and somehow MCA result provides more efficient work program compared to economic analysis.